PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PROBLEM BASED LEARNING PADA SISWA KELAS VI SDN 17 BENGKALIS - Ismail Ismail (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is in the background by the still low student learning outcomes and students' learning interest that is still lacking, thus causing learning completeness students are not able to achieve the completeness value that has been set by the school. The form of this research is classroom action research in order to improve the learning process in the classroom. This study aims to improve the learning outcomes of science in class VI SDN 017 Bengkalis. The results of the study were by applying the problem based learning learning model, the learning outcomes of science improved. Data obtained after research on teacher activity in the first cycle of the 1st meeting with a percentage of 63%, the second meeting with a percentage of 77%, in the second cycle at the third meeting percentage by 80%, and at the 4th meeting the percentage obtained 94%. Student observation data in this study obtained the percentage of the first cycle of the first meeting was 67%, the second meeting was 80%, in the second cycle the third meeting was 85%, and the 4th meeting obtained a percentage of 90% this proved that student activity has increased. Data on the increase in student learning outcomes in class VI SDN 017 Bengkalis in the initial data obtained an average of 65, on the daily test I obtained a class average of 80, and in the daily test II obtained an average of 95 this proves that the use of problem learning models based learning can improve learning outcomes of class VI SDN 017 Bengkalis.